2020
DOI: 10.1111/trf.15815
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion safety in the country of Georgia: collateral benefit from a national hepatitis C elimination program

Abstract: BACKGROUND In April 2015, the government of Georgia (country) initiated the worldʼs first national hepatitis C elimination program. An analysis of blood donor infectious screening data was conducted to inform a strategic plan to advance blood transfusion safety in Georgia. STUDY DESIGN AND METHODS Descriptive analysis of blood donation records (2015‐2017) was performed to elucidate differences in demographics, donor type, remuneration status, and seroprevalence for infectious markers (hepatitis C virus antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Even though universal HCV antibody screening of blood donations in Georgia started in 1997, our previous analysis found that receiving a blood transfusion after 1997 was still associated with high anti-HCV prevalence, suggesting the need for further improvements in blood safety [24]. However, a recent analysis of blood transfusion programs in Georgia showed positive trends in blood safety since 2015, suggestive of collateral benefit from a national hepatitis C elimination program [30].…”
Section: Discussionmentioning
confidence: 93%
“…Even though universal HCV antibody screening of blood donations in Georgia started in 1997, our previous analysis found that receiving a blood transfusion after 1997 was still associated with high anti-HCV prevalence, suggesting the need for further improvements in blood safety [24]. However, a recent analysis of blood transfusion programs in Georgia showed positive trends in blood safety since 2015, suggestive of collateral benefit from a national hepatitis C elimination program [30].…”
Section: Discussionmentioning
confidence: 93%
“…Manyif not most -CCP donors are expected to be first-time donors and will be unfamiliar with the donation process. First-time donor status introduces considerations of risk: first-time donors are higher risk of TTIs and donation-associated adverse events than repeat donors [23][24][25][26][27]. Repeat donation selects for healthier individuals as criteria for donation (e.g.…”
Section: Donor Recruitmentmentioning
confidence: 99%
“…PR would allay concerns related to viral transmission from CCP. Pertinent to LMICs, CCP donors are more likely to be first-time donors and thus have a higher risk of TTIs [23,[25][26][27]. In countries that issue recovered FFP through a quarantine system routinely, PR would address the risk of a the major TTIs (e.g.…”
Section: Pathogen Reductionmentioning
confidence: 99%
“…This article is a US Government work. It is not subject to copyright under 17 USC 105 and is also made available diagnostic and treatment services for TB countrywide [26,[28][29][30][31]…”
Section: Introductionmentioning
confidence: 99%